Analysis of the Application of CPM, Monte Carlo Simulation, and EVM Methods on Time and Cost Estimation for Infrastructure Project Development (Case Study: Culvert Construction) - Wildan Hilman (Return : Study of Management, Economic and Bussines, 2025)
This research examines the application of the Critical Path Method (CPM), Program Evaluation and Review Technique (PERT), and Earned Value Management (EVM) in estimating the time and cost of infrastructure projects, specifically in the construction of culverts. The study integrates Monte Carlo simulations to assess risks and uncertainties associated with project time and cost. By utilizing these methods, the study aims to provide accurate estimations and optimize project management strategies to mitigate delays and cost overruns. The findings demonstrate that integrating CPM and PERT can significantly enhance project planning, scheduling, and cost control, reducing time discrepancies and improving cost efficiency. Furthermore, Monte Carlo simulations offer probabilistic insights into the project's performance, while EVM provides a real-time monitoring tool for evaluating project execution. This research contributes to the improvement of infrastructure project management by offering a systematic approach to handle uncertainties and ensure more reliable project outcomes.